Innovative foresight as a tool for shaping development strategy business structures (Путеводитель предпринимателя, 2020)
To obtain stable and distinctive competitive advantages that make strategic competitiveness, entrepreneurs must have the knowledge-component development, including the ability to produce and innovate in their management systems. The article discusses the innovative foresight as an effective tool of the active construction of future business structures for the formation of strategic competitiveness in the long term.